1871 Tex. Gen. Laws 14, An Act To Incorporate The Town Of Millican, County of Brazos, Art. 10 - (:unkn) unknown (General Publisher, 1871)
That from and after the passage of this act it shall be unlawful to fire any pistol, rifle, shot gun, or other kind of firearms, within the limits of the town of Millican, and any person violating this act shall be fined not less than five nor more then twenty-five dollars...
--
Keywords: DISCHARGE